Epoxyeicosatrienoic acid analog EET-B attenuates post-myocardial infarction remodeling in spontaneously hypertensive rats - Neckář, Jan; Hye Khan, Md Abdul; Gross, Garrett J; Cyprová, Michaela; Hrdlička, Jaroslav; Kvasilová, Alena; Falck, John R; Campbell, William B; Sedláková, Lenka; Škutová, Šárka; Olejníčková, Veronika; Gregorovičová, Martina; et al. (Clinical science (London, England, 2019)
Epoxyeicosatrienoic acids (EETs) and their synthetic analogs have cardiovascular protective effects. Here, we investigated the action of a novel EET analog EET-B on the progression of post-myocardial infarction (MI) heart failure in spontaneously hypertensive rats (SHR). Adult male SHR were divided into vehicle- and EET-B (10 mg/kg/day; p.o., 9 weeks)-treated groups. After 2 weeks of treatment, rats were subjected to 30-min left coronary artery occlusion or sham operation. Systolic blood pressure (SBP) and echocardiography (ECHO) measurements were performed at the beginning of study, 4 days before, and 7 weeks after MI. At the end of the study, tissue samples were collected for histological and biochemical analyses. We demonstrated that EET-B treatment did not affect blood pressure and cardiac parameters in SHR prior to MI. Fractional shortening (FS) was decreased to 18.4 ± 1.0% in vehicle-treated MI rats compared with corresponding sham (30.6 ± 1.0%) 7 weeks following MI induction. In infarcted SHR hearts, EET-B treatment improved FS (23.7 ± 0.7%), markedly increased heme oxygenase-1 (HO-1) immunopositivity in cardiomyocytes and reduced cardiac inflammation and fibrosis (by 13 and 19%, respectively). In conclusion, these findings suggest that EET analog EET-B has beneficial therapeutic actions to reduce cardiac remodeling in SHR subjected to MI.
Keywords: modely nemocí na zvířatech; kyseliny arachidonové; Male; heart failure; hemoxygenasa-1; srdce; potkani inbrední SHR; mužské pohlaví; blood pressure; myocardial infarction; infarkt myokardu; krysa rodu Rattus; Animals; lidé; krevní tlak; Humans; zvířata; Myocardial Infarction; Rats; Blood Pressure; Disease Models, Animal; Arachidonic Acids; Rats, Inbred SHR; spontaneously hypertensive rat; epoxyeicosatrienoic acid; Heart; Heme Oxygenase-1